Enforced Electrocatalytic Oxidation of Low Concentration of Phenol On the Porous Ceramic Tube Based Electrode Supported With Platinum Nanoparticles - Zheng, Yuying; Liao, Shijun; Mo, Zaiyong; Yang, Xu; Liu, Quanbing (Current Nanoscience, 2013)
The removal of phenolic solution is of great importance for the treatment of industrial waste water and the purification of drink water. By carbonizing an alumina porous tube and depositing platinum nanoparticles on the ex/interior surface, a novel enforced porous ceramic tubular electrode, Pt/C/Tub-Al2O3, was prepared and used for the removal of phenol contained waste water via enforced electrocatalytic oxidation process. Excellent removal efficiency has been achieved at 2.0V of applied cell voltage, and temperature of 40 ºC. No obvious performance attenuation can be observed after 10 times recycle utilization, which can be attributed to the structure features of porous membrane, high dispersed Pt nanoparticles and good conductivity. N2 sorption, XRD, SEM/TEM and cyclic voltammetry measurements were performed to characterize the structure of Pt/C/Tub-Al2O3 electrode. The enforced oxidation with this tubular porous electrode may provide an effective candidate technique for the removal of phenol from waste water.
Keywords: Electrocatalyst